Information and Communications Security 11th International Conference, ICICS 2009 - Qing, Sihan; Mitchell, Chris J.; Wang, Guilin (Security and Cryptology, 2009)
This book constitutes the refereed proceedings of the 11th International Conference on Information and Communications Security, ICICS 2009, held in Beijing, China, in December 2009. The 37 revised full papers presented together with one invited paper were carefully reviewed and selected from 162 submissions. The papers are organized in topical sections on cryptanalysis, algorithms and implemantations, public key cryptography, security applications, software security, system security, network security, database security, trust management, and applied cryptography.